Pengaruh Pemberian Kinesio Taping dan Es Terhadap Penurunan Nyeri Sprain Ankle pada Pemain Futsal - Nugraha, Restu Aji; , Wahyuni, SSt.FT.M.Kes; , Sugiono S.Fis.MH.Kes (2017)
Background: Injuries that often happen in the futsal field is ankle sprain, since the player of futsal often use movements that involve legs. Several modalities that can be applied are Kinesio taping and ice to assist in the reduction of pain in a variety of conditions such as ankle sprain. Research Objective: This research was done to determine the benefits of kinesio taping and ice on the sprain ankle reduction of futsal players. Research Method: This research is a Quasi Experimental of one group pre and post test method without control design. This research applied one group of research subjects, without using control group to determine the effect of kinesio taping and ice application on the sprain ankle. The measurements of pain was done by using VAS, whereas to determine the effect of the application of Kinesio taping and ice on ankle sprain was done by using data analysis of Wilcoxon Signed Rank Test. Results: The results obtained from the statistic test of Wilcoxon Signed Rank Test, show the value of (Asymp. Sig 2 tailed) is 0,039 which is less than the critical limit of 0.05 (sig 0.039 <0.05), therefore, H1 is accepted, that there is a significant difference between the groups pre-test and post-test. Conclusion: There is a significant effect of kinesio taping and ice application on the sprain ankle. Keywords: Kinesio taping, ice, sprain ankle, VAS, futsal players